2022
DOI: 10.1002/saj2.20420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Achnatherum inebrians ecotypes and endophyte status on plant growth, plant nutrient, soil fertility and soil microbial community

Abstract: Effects of endophytes infection on bacterial and fungal communities in soil have been extensively studied. However, how the presence of Epichloë endophytes and environmental factors influence the nitrifying genes abundance of ammonia-oxidizing archaea (amoA-AOA) and bacteria (amoA-AOB), and denitrifying genes abundances of N reduction (nirS and nirK) and nitrous oxide reduction (nosZ) in soil is unclear. In the study, the copy number of 16S rRNA, 18S rRNA, amoA-AOB, amoA-AOA, nirS, nirK, and nosZ genes in rhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 118 publications
0
0
0
Order By: Relevance
“…In the present study, after a four-day incubation, it was observed that bacterial community structure, rather than total bacterial abundance, showed a stronger response to fertilization. Nitrogen fertilization has been demonstrated to be a significant factor in shaping soil microbial community (Yuan et al, 2015;Wu et al, 2021;Jin et al, 2022), probably by providing substrates and energy sources for indigenous microbes or due to nutrients imbalances resulting from a pulse input of N (Eo and Park, 2016). The bacterial abundance remained relatively stable after the 96-h incubation, which is consistent with the fact that soil bacteria generally have very slow growth rates, with a doubling time being over 100 days (Harris and Paul, 1994).…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, after a four-day incubation, it was observed that bacterial community structure, rather than total bacterial abundance, showed a stronger response to fertilization. Nitrogen fertilization has been demonstrated to be a significant factor in shaping soil microbial community (Yuan et al, 2015;Wu et al, 2021;Jin et al, 2022), probably by providing substrates and energy sources for indigenous microbes or due to nutrients imbalances resulting from a pulse input of N (Eo and Park, 2016). The bacterial abundance remained relatively stable after the 96-h incubation, which is consistent with the fact that soil bacteria generally have very slow growth rates, with a doubling time being over 100 days (Harris and Paul, 1994).…”
Section: Discussionsupporting
confidence: 54%